1993
DOI: 10.1093/oxfordjournals.annonc.a058654
|View full text |Cite
|
Sign up to set email alerts
|

The teaching of clinical oncology in Italian medical schools. A survey among teachers and students

Abstract: This survey emphasizes the dualism between students' expectations and teachers' ideas about cancer teaching. Doctor/patient relationships and poor attention to practical clinical problems seem the most critical issues for clinical oncology training in Italian medical schools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Most of these prior studies concluded that medical students were exposed to insufficient numbers of cancer patients during their training and ultimately lacked basic knowledge about cancer. [10][11][12][13][14][15][16][17] These inadequacies in oncology education inevitably resulted in physicians who felt poorly prepared to handle cancer patients in their routine practice. 10 The current study confirms these previous findings, but it is the first to address the quality of oncology education in several other health disciplines.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these prior studies concluded that medical students were exposed to insufficient numbers of cancer patients during their training and ultimately lacked basic knowledge about cancer. [10][11][12][13][14][15][16][17] These inadequacies in oncology education inevitably resulted in physicians who felt poorly prepared to handle cancer patients in their routine practice. 10 The current study confirms these previous findings, but it is the first to address the quality of oncology education in several other health disciplines.…”
Section: Discussionmentioning
confidence: 99%
“…Surveys in Europe (Haagedoorn, 1985;Bender et al, 1993;Cellerino et al, 1993;Ramakrishnan et al 1993), the USA (Bakemeier, 1981), and Australia (Tattersall et al, 1993;Barton and Simons, 1999) have all identified problems with undergraduate oncology teaching including inadequate coordination, insufficient resources, and variability in the curriculum (UICC, 1994). Several methods for teaching students about oncology have been evaluated (Gaffan et al, 2006), but there is little published evidence to guide the choice of content.…”
mentioning
confidence: 99%
“…41,42 Clinical practice was preferred to more innovative teaching methods such as problem-based sessions and computer aided learning, with students showing significantly higher interview and clinical skills scores using the former. 25,27,34,36 Kissane et al reported a similar relationship with lectures and pre-planned classroom time as well. 26 Structured clinical experience was also rated more highly (92%) than both lectures (80%) and small group discussions (72%) on similar topics.…”
mentioning
confidence: 85%
“…Cellerino et al observed that these traditional teaching methods were preferred over more innovative approaches, such as problem-solving case discussions and web-based learning. 27 These combined sessions significantly improved test averages by 43% (P < 0.001) and 11% (P < 0.05) respectively as well as increased basic knowledge of dermatologic cancers. 28,29 Liu et al did not observe this with more advanced topics such as staging.…”
mentioning
confidence: 88%